Hope in a depression therapeutic group: a qualitative case study - Ana Isabel Fernandes Querido; Carlos António Laranjeira; Maria dos Anjos Coelho Rodrigues Dixe (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to understand the perceptions of hope for people with depression in the context of a therapy group. Methods: using a qualitative case study approach, a semi-structured in-depth interview and a self-report questionnaire were conducted with seven women with depression integrated in a therapy group at a Portuguese day-care psychiatric unit. Data collection and analysis used triangulation of sources. Results: the participants evidenced hope founded on the positive experiences of the past with a strong affiliation component. Hope management is done fundamentally through the interpersonal relationships established between the members of the group, based on communicational patterns that are established on a regular basis, mediated by the group therapist. Conclusion: the therapy group functioned towards the reinforcement of hope in people who experience depression, and it works as a motivation to manage the implications of illness in the participants' life and health project.